The effect of culture media and seeding densities on the human malignant testicular germ cell line (NT2/D1) growth pattern - Rawabi S. Altuwayjiri; Ibtesam S. Almami (Journal of Biological Research)
Testicular cancer is a common malignancy in young males, comprising 5% of urological cancers and 1% of all male cancers. The NT2/D1 cell line, a pluripotent embryonal carcinoma, is valuable in cancer and developmental biology research due to its differentiation potential into neurons and glial cells. Although Fetal Bovine Serum (FBS) is often used to promote cell growth, its limitations necessitate optimized culture conditions. Monitoring cell growth and health through methods such as cell counting, viability assays, growth curves, and microscopy is crucial for reliable research, particularly for evaluating specific cell characteristics before in vitro studies. The study compared the growth patterns of NT2/D1 cell lines under different culture conditions and seeding densities using trypan blue cell counting and MTT methods. The NT2/D1 cell lines cultured in heat-inactivated FBS (H.iFBS) and non-heat-inactivated FBS (Non-H.iFBS) exhibit distinct growth patterns, doubling times, and cell morphologies. Cell density and the condition of the culture medium are two key parameters influencing metabolic activities and enhancing variability. There is no preference between culturing cells in different FBS conditions yet it should be considered in experiment design. Thus systematic reporting of all cell culture parameters is essential to facilitate better comparisons of in vitro and in vivo experimental data.